A Novel Niosomal Doxycycline/Triamcinolone Medicament Matches Calcium Hydroxide for Low Tooth Staining: A 4-Week in Vitro Study - Fereidooni, Rahim; Shahravan, Arash; Manochehrifar, Hamed; Pardakhty, Abbas; Kamyabi, Homa; Nekouei, Amir Hossein (Iranian Endodontic Journal, 2025)
Introduction: Tooth discoloration remains a significant concern in endodontic treatment, particularly with the use of intracanal medicaments. This study investigated the discoloration potential of niosomal doxycycline and triamcinolone, a novel nanotechnology-based drug delivery system, in comparison to conventional medications. Materials and Methods: Fifty extracted single-rooted human teeth were assigned to five groups: (1) calcium hydroxide, (2) calcium hydroxide+triamcinolone, (3) niosomal doxycycline+triamcinolone, (4) doxycycline+triamcinolone, and control groups (positive: blood; negative: saline). All samples were prepared using standardized endodontic procedures, filled with medicaments, and incubated for one month. Discoloration values (∆E) were measured at baseline, 1 week, and 1 month using the CIE Lab system and a spectrophotometer. A ∆E>3.3 was considered clinically unacceptable. Results: All groups exhibited discoloration values within clinically acceptable limits (∆E<3.3). At one month, significant differences were observed among groups (ANOVA, P<0.05). The niosomal doxycycline+triamcinolone group showed the lowest ∆E values, similar to the calcium hydroxide group, while the doxycycline+triamcinolone and calcium hydroxide+triamcinolone groups exhibited higher discoloration values. Conclusion: Emphasize that at 4 weeks, all medicaments induced clinically acceptable ∆E, with niosomal performing similarly to calcium hydroxide alone and significantly better than the conventional doxycycline+triamcinolone combination.